Climate Change in Sustainable Water Resources Management - Bozorg-Haddad, Omid. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book provides a comprehensive approach to all aspects of water-related subjects affected by climate change that expand readers' attitudes toward future of the management strategies and improve management plans. It summarizes climate change scenarios, models, downscaling methods, and how to select the appropriate method. It also introduces practical steps in assessing climate change impacts on water issues through introducing hydrological models and climate change data applications in hydrologic analysis. The book caters to specialist readers who are interested in analyzing climate change effects on water resources, and related issues can gain a profound understanding of the practical concepts and step-by-step analysis, which is enriched with real case studies all around the world. Moreover, readers will be familiar with potential mitigation and adaptation measures in sustainable water engineering, considering the results of hydrologic modeling.
Overview of climate change in water resources management studies -- Basic concepts -- Climate Change Drivers -- The Effect of Climate Change on Water Resources -- Review on IPCC reports -- Introduction to Key Features of Climate Models -- Downscaling Methods -- Hydrological models -- Mitigation and Adaptation Measures -- Case Studies Around the World.
Keywords: Water; Hydrology; Environmental management; Sustainability; Water; Environmental Management; Sustainability